Seismic evaluation and retrofit of reinforced concrete structures - Mangeshkumar R. Shendkar; Adithya Tantri; Asha Udaya Rao (Journal of Infrastructure Preservation and Resilience)
Abstract The destructive earthquakes in the world clearly reveal the importance of the seismic behavior of the structures. The current study proposes and numerically investigates a systematic technique for the seismic assessment and retrofit of reinforced-concrete buildings according to both material strain limit approach and Quadrants assessment method. In this study numerical analysis were made for two three-dimensional building models, namely a single-storey 30 years old existing RC building in Koyna-Warna area (Zone-IV) in India, and an earthquake-resistant designed 4-story RC building. The structural analyses were performed for two 3-D models of the selected buildings are analysed. Nonlinear static adaptive pushover analysis method was used in Seismostruct software program for two different buildings. While one of the buildings is an existing building, the other is chosen as a new building. Structural characteristics and deficiencies of the investigated single-storey existing reinforced-concrete structure necessitated seismic evaluation. The deficiencies include pitched roofs, re-entrant corners, and structural distress such as structural element cracking and cover concrete spalling, among others. The single-story RC building is retrofitted with RC jacketing and fiber-reinforced polymer sheet wrapping, while the four-storey RC building does not need to be retrofitted based on the Quadrants assessment method. Also, the significant seismic design parameters are evaluated before and after the retrofit. The results show that the material strain limit technique when combined with the Quadrants assessment method makes a more efficient technique for seismic assessment and retrofit purpose. Also, the ultimate capacity and over strength factor of the retrofitted single-storey RC existing building are found 2.04 times and 1.82 times increased in X and Y direction as compared to the building without retrofit, because of the RC jacketing and FRP sheet wrapping.